To identify how service quality and brand image impact on customer satisfaction and customer loyalty in China's mobile phone markets on youth consumers. - Wang, Yuyao (2007)
The relationship between service quality and customer satisfaction Many theorists have suggested that high customer expectations of service quality can lead to better service performance which, in turn, positively influences customer satisfaction with service. This can then perpetuate a cycle of positive reinforcing behavior. Cronin and Taylor (1992) mentioned that there is a preponderance of evidence that service quality is an antecedent to service satisfaction. Rust and Oliver (1994) describe customer satisfaction as being a reaction to a service incident (or long-term service relationship.) The relationship between brand image and customer satisfaction Different brand have a differing quality reputation, the author expects the service quality to be directly related to the brand type. The effect of brand name on consumer perceptions is viewed in the marketing literature as a signaling effect. Rao and Monroe (1999) empirically examine this relationship and find a positive relationship between quality reputation associated with the brand and consumer perceptions of quality. Among the established signals of quality (brand, price, physical appearance, and store name), brand was found to be the most important (Dawar and Parker, 1994). The relationship between customer satisfaction and customer loyalty Anderson and Sullivan (1993), in analyzing data from a study of customer satisfaction among Swedish customers, find that stated customer loyalty is strongly related to stated satisfaction across product categories. A study conducted by Woodside, Frey, and Daly (2000) uncovers a significant association between overall patient satisfaction and intent to choose the hospital again. Research frame and the linkage to the project In order to implement an efficient and sustainable aim, this research will be built upon a conceptual framework based on the research motive, objectives and literature review described above. Since the aim of this research is to identify how service quality and brand image impact on customer satisfaction and customer loyalty in China's mobile phone markets on youth generation, a comprehensive literature review has been examined the above four aspects in detail and the inter-links have also been unrevealed. The literature review has set up a holistic theory frame to lay a foundation for the author to do further research and evaluate the theories discussed in this chapter. For example, through examining the literature review, the author found many theorists have done some research on the correlation among the four dimensions and some of the research results have been put forward at the end of this chapter, which reflect the objective 1 and also is the source of the hypotheses that will be raised in the next chapter. The literature review chapter also has provided the theoretical support and tools for the author to evaluate the customer service. As the industry focus on customers and providing service, keeping brand image, building brand loyalty and improving customer service is the major tasks of any mobile phone maker. Therefore, the author will focus on the emphasis of the literature review when conducting the survey, analyzing the current situation of the industry, discovering problems and developing relevant strategies. Considering these different theories and studies, mobile phone industry in China will be able to come across with a more spherical view and choose the best way for the future development.